Information Technology and Health Management: The case of the implementation of a computer system for payments of employees in the public sector - Nerio , Valeria Romão Pasqualini; Gomes , Maria Morgana Souza; Franco , Jadson; Rodrigues , Claudiane Bezerra (Seven Editora, 2023)
At the School of Public Health of Ceará Paulo Marcelo Martins Rodrigues - ESP/CE, an autarchy of the Secretariat of Health of the State of Ceará - Sesa, the process of payment of scholarships of the institution previously carried out involving the use of paper, being an onerous process, followed by physical processing in the sectors involved in its administrative flow. These work circumstances involved excessive consumption of paper and sometimes rework with pending signatures and physical documents, leading to delays in the payment process. In this context, this article aims to describe the experience of the implementation of the so-called Single Integrated System of Electronic Processing - SUITE in the Health Research Management (GEPES) of ESP/CE, during 1 semester, for the process of payment of scholarships, which represents approximately 83% of the workforce of the sector. It was possible to conclude that the insertion of a computer system optimized the process of payment of employees, with the reduction of 30 days in the time-lapse for the execution of this task, as well as the reduction of 100% of paper used for this type of process, conferring greater efficiency and economy in health management. DOI:https://doi.org/10.56238/alookdevelopv1-138